Why Does This Learner Perform Poorly on Tests? Using Self-Regulated Learning Theory to Diagnose the Problem and Implement Solutions. (April 2018) - Andrews, Mary A.; Kelly, William F.; DeZee, Kent J.
Abstract : Problem: Learners who underperform on standardized tests are common throughout all levels of medical education and require considerable faculty time and effort to remediate. Current methods for remediating test-taking difficulties are typically not grounded in educational theory or supported by high-quality evidence. Approach: A test-taking assessment was developed based on self-regulated learning (SRL) microanalytic assessment and training and used during academic year 2012–2013. This method assesses the SRL subprocesses of strategic planning, self-monitoring, causal attributions, and adaptive inferences during the educational task of answering test questions. The method was designed for one-on-one use by teacher and learner, and for learner self-assessment and practice. Outcomes: At one academic institution, this method was used to categorize learners into struggling test-taker subtypes which correspond to deficiencies in the SRL subprocesses outlined above. A learning plan based on the SRL deficiency was developed for each struggling test-taker subtype. In a small number of internal medicine residents with low in-training examination scores, use of this method yielded improvements in 2013 in-training examination score that doubled the expected improvement based on historical averages. Next Steps: This method is a novel application of SRL theory to a commonly encountered problem in medical education: the learner who performs poorly on tests. Large-scale, multicenter studies of medical learners at a variety of training levels and program types are needed to determine the effectiveness and generalizability of this intervention. Abstract : Supplemental Digital Content is available in the text.